The impact of out-of pocket payments of households for dental healthcare services on catastrophic healthcare expenditure in Iran - Woldemichael, Abraha (BMC Public Health, 2021)
BACKGROUND: Dental healthcare is the costliest and single most source of the financial barrier to seeking and use of needed healthcare. Hence, this study aims to analyses impact of out-of-pocket (OOP) payments for dental services on prevalence catastrophic healthcare expenditure (CHE) among Iranian households during 2018. METHODS: We performed a cross-sectional analysis to determine the prevalence rate of CHE due to use of dental healthcare services among 38,858 Iranian households using the 2018 Household Income and Expenditure Survey (HIES) survey data of Iran. The WHO approach was used to determine the CHE due to use of dental care services at the 40% of household capacity to pay (CTP). Multiple logistic regression models were used to obtain the odds of facing with CHE among households that paid for any dental healthcare services over the last month while adjusting for covariates included in the model. These findings were reported for urban, rural areas and also for low, middle and high human development index HDI across provinces. RESULTS: The study indicated that the prevalence of CHE among households that used and did not used dental services over the last month was 16.5% (95% CI: 14.9 to 18.3) and 4.3% (95% CI: 4.1 to 4.6), respectively. The adjusted odds ratio (AOR) for the covariates revealed that the prevalence of CHE for the overall households that used dental healthcare service was 6.2 times (95% CI: 5.4 to 7.1) than those that did not use dental healthcare services. The urban households that used dental healthcare had 7.8 times (95%CI: 6.4–9.4) while the rural ones had 4.7 times (95% CI: 3.7–5.7) higher odds of facing CHE than the corresponding households that did not use dental healthcare services. CONCLUSIONS: The study indicates that out-of-pocket costs for dental care services impose a substantial financial burden on household’s budgets at the national and subnational levels. Alternative health care financing strategies and policies targeted to the reduction in CHE in general and CHE due to dental services in particular are urgently required in low and middle income countries such as Iran. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12889-021-11209-6.